3D Fluorescence‐Based Security Features by 3D Laser Lithography. Issue 11 (21st September 2017) - Mayer, Frederik; Richter, Stefan; Hübner, Philipp; Jabbour, Toufic; Wegener, Martin
Abstract: 3D optical security features manufactured by multistep 3D optical laser lithography are presented. These microstructures are composed of a nonfluorescent 3D cross‐grid scaffold and fluorescent markers, realized by an acrylate‐based resist containing CdSSe‐based core–shell semiconductor quantum dots, arranged onto this scaffold at will. The readout of these 3D microstructures can be (exclusively) achieved by optical sectioning methods, for example, 3D confocal fluorescence laser scanning microscopy. As examples, structures with five different layers of markers and one emission color and two different colors, respectively, are shown. This class of deterministic 3D microstructures can be embedded into thin polymer films, can be individualized, and allows for plenty of future variations and extensions. It therefore represents an interesting avenue beyond established 2D holographic or 2D fluorescent optical security features. Abstract : Fluorescent 3D optical security features manufactured by multistep 3D optical laser lithography are presented. These microstructures are composed of a nonfluorescent 3D cross‐grid scaffold and fluorescent markers, arranged onto this scaffold at will. They can (exclusively) be readout by 3D confocal fluorescence laser scanning microscopy. As examples, structures with up to two different emission colors are demonstrated.